ANALISIS HUBUNGAN STATUS GIZI DAN INDEKS PRESTASIKUMULATIF (IPK) MAHASISWA KEBIDANAN DIPLOMA III - Rinjani, Shita; Nirmala, Sefita Aryuti; Martini, Neneng; Rinawan, Fedri R.; Gumilang, Lani (Jurnal Vokasi Indonesia, 2020)
Building the quality human resources can be ordered through higher education both vocational and bachelor pathways, up to master and doctoral levels. Midwifery students as health students are also youth and national movers who are the most important assets for national development. No denying midwife student activities require good time management equipped with mental and psychological preparation. Physical preparation can be prepared with nutritional needs being met so that nutritional status is good, so that good academic activities can be obtained and the GPA obtained. Students must get the maximum learning process so that they get good quality education and are supported by good food intake so that the nutritional status of students is fulfilled. Because nutrition and food are one of the most important factors in developing the quality of human resources which can affect brain intelligence. This research aims to determine the relationship between nutritional status and GPA of midwifery students in Bandung used a quantitative approach with a cross sectional study design. The number of respondents was 105 people. Determination of nutritional status was obtained from BMI (body mass index) parameters with BB/TB2 . The student's GPA was known from the KPA (academic achievement card). The statistical test used is the Spearman rank. Statistical test results showed no relationship between nutritional status with GPA (p = 0.176).